A RARE CASE OF ODONTOGENIC PARAINFECTIOUS INTRAORBITAL OPTIC NEURITIS WITH THE ABSENCE OF CLINICAL MANIFESTATION OF ORBITAL CELLULITIS. Issue Volume 9:Issues 3(2015:Summer) (2015) - Vu, Qui; Dyer, Gawain; Kunjukunju, Nancy
Abstract : Purpose: To report the case of a 67-year-old male patient with odontogenic maxillary sinusitis who presented with unilateral parainfectious intraorbital optic neuritis without clinical signs and symptoms suggestive of orbital cellulitis. Despite the absence of clinical signs, taking a thorough history and obtaining the appropriate neuroimaging study raised the suspicion for an infectious etiology as the cause of optic neuropathy and stopped the continuation of corticosteroid treatment. Methods: Retrospective case report. Results: The only abnormal findings in the ophthalmic examination were acute decrease visual acuity, inferior visual field loss, and the presence of a relative afferent pupillary defect. A gadolinium contrast-enhanced magnetic resonance imaging scan showed ill-defined diffuse enhancement of the left intraorbital optic nerve and sheath with mild perineural fat stranding and enlargement of the inferior rectus muscle. There was also complete opacification of the ipsilateral maxillary sinus with peripheral enhancement, suggestive of a sinus abscess. Conclusion: Prompt arrival to the diagnosis led to expedient implementation of treatment comprising of broad-spectrum intravenous antibiotics and maxillary sinus irrigation by otolaryngology ultimately resulted in restoring the patient's vision back to baseline with complete resolution of the relative afferent pupillary defect. Abstract : We describe a patient presenting with a history of recent dental abscess, acute painless vision loss, and relative afferent pupillary defect with complete absence of clinical orbital signs. However, magnetic resonance imaging showing enlargement of the inferior rectus muscle, presence of perineural fat stranding, and diffuse intraorbital optic nerve and sheath enhancement, corroborated our suspicion for a case of odontogenic parainfectious intraorbital optic neuritis.